2023
DOI: 10.3390/min13020294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Sulfate Solution on Pore Structure of Ionic Rare Earth Ore during Leaching Process

Abstract: During in situ leaching of ionic rare earth ore, the pore structure of the orebody changes due to the chemical replacement reaction between the leaching agent and the rare earth ore. To explore the influence of leaching agents on the pore structure of ionic rare earth ore during the leaching process, magnesium sulfate solutions with different concentrations and pH are used as leaching agents in this paper. An experimental method of indoor simulated column leaching, a Zetaprobe potential analyzer, and an NM-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The gas in the pores was gradually replaced by pore solution, and the pore solution volume, the saturation, and the conductive path 2 in Figure 2 increased. The micro and small pores in the ore body evolved into medium and large pores under the action of seepage, and the pore size of the ore body increased, the seepage effect was enhanced, and the solution connectivity was improved [51][52][53][54][55]. Due to the continuous addition of ammonium sulfate leaching solution, the number of ions in the pore solution increased, and the improvement in pore connectivity led to an increase in the freely moving anion number in the solution, so the conductive capacity of the solution was enhanced.…”
Section: Equivalent Circuit Parameter Analysismentioning
confidence: 99%
“…The gas in the pores was gradually replaced by pore solution, and the pore solution volume, the saturation, and the conductive path 2 in Figure 2 increased. The micro and small pores in the ore body evolved into medium and large pores under the action of seepage, and the pore size of the ore body increased, the seepage effect was enhanced, and the solution connectivity was improved [51][52][53][54][55]. Due to the continuous addition of ammonium sulfate leaching solution, the number of ions in the pore solution increased, and the improvement in pore connectivity led to an increase in the freely moving anion number in the solution, so the conductive capacity of the solution was enhanced.…”
Section: Equivalent Circuit Parameter Analysismentioning
confidence: 99%
“…The variation of surface potential was also the largest, increasing by 49.77%. Due to the strong hydrophobicity of the surface of rare earth minerals, more Mg 2+ entered the particle surface, and the ionized impurity ions were adsorbed onto the particle surface to compress the double layer, resulting in a decrease in the absolute value of Zeta potential [5,38,39].…”
Section: Comparative Analysis Of Zeta Potential and Surface Potential...mentioning
confidence: 99%
“…It mainly exists on the surface of minerals in the form of ions, such as halloysite, illite, kaolinite, and a small amount of montmorillonite in the deposit. The only way to extract rare earth elements is to use a salt electrolyte solution to leach ion-adsorbed rare earth deposits [2][3][4][5]. Flotation is usually used to pre-treat ores containing valuable metals before leaching [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, only the process from non-saturation to saturation of the ore sample was tested. Gao et al [26] found that the porosity did not change during the saturation process when the ore was leached with clean water. Thus, the test was not conducted after saturation.…”
Section: Fitting and Analysis Of Swccmentioning
confidence: 99%